Quality characteristics of pork loin cured with green nitrite source and some organic acids. (June 2019) - Kim, Tae-Kyung; Hwang, Ko-Eun; Lee, Mi-Ai; Paik, Hyun-Dong; Kim, Young-Boong; Choi, Yun-Sang
Abstract: This study was conducted to improve the quality characteristics of cured meat with natural nitrite. Control and treatment were conducted as follows: nitrite free, marinated with sodium nitrite and ascorbic acid, marinated with only fermented spinach (FS), and marinated with FS adding ascorbic acid, malic acid, citric acid, and tartaric acid. Treatments were pickled with regulated brine (8% salt and 0.08% nitrite). Cured meat with FS adding ascorbic acid, malic acid, and citric acid had higher redness values than sodium nitrite with ascorbic acid on cooked meat. There was a positive effect on lipid oxidation except for citric acid. Protein degradation appeared more in malic acid and tartaric acid treatment than others. Residual nitrite level was lower when adding organic acids. Among various organic acid, ascorbic acid had the highest efficient on quality properties of cured meat. Thus, ascorbic acid was a proper ingredient when curing meat product. Highlights: Improvement of curing efficiency using organic acids. Residual nitrite and color coupling were evaluated. Meat cured with natural nitrite source was analyzed. Determination of organic acids added to a meat product.